Investigação das atividades mutagênica, antimutagênica e antioxidante de extratos etanólicos de Aiouea trinervis, Nectandra cissiflora, Ocotea minarum (Lauraceae) e dos alcalóides triptofol, ocoteína e dicentrina - Guterres, Zaira da Rosa (2008)
The Brazilian cerrado (tropical American savanna) is a semi-arid region in which plants are submitted to metabolic stress that triggers defense mechanisms when confronted with unfavorable environmental conditions. The Lauraceae is an economically important family with 52 genera and approximately 2500-2750 species consisting mostly of trees or tree-like shrubs, rich in biologically active secondary metabolites, such as lignans (sesamin, methylpiperitol and polyprenol-12), g-lactones (isoobtusilactone), alkaloids, flavonoids and terpenes, which have shown different biological and pharmacological activities. Several plants from Lauraceae family are considered endangered Brazilian cerrado species. According to studies conducted in the area of phytochemistry at the Chemical Department of the Federal University of Mato Grosso do Sul (UFMS), using the three species Aiouea trinervis, Nectandra cissiflora and Ocotea minarum several secondary metabolites have been already isolated, so the aim of the present study was to verify: i] the antioxidant activity of ethanolic extracts (EE) obtained from the leaves of Aiouea trinervis and from the leaves or stems of Nectandra cissiflora; 2] the genotoxic effects (evaluated for mutagenic and recombinagenic effects) of EE obtained from the leaves or fruits of Aiouea trinervis, from leaves or stems of N. cissiflora, and g-lactones from fruits of A. trinervis; 3] the antimutagenic effects of EE obtained from leaves of A. trinervis and from leaves or stems of N. cissiflora. The antioxidant activities were evaluated in vitro using the 2,2-diphenyl-1- picrylhydrazyl (DPPH) free radical scavenging method. The data observed with DPPH test demonstrates antiradical activity of plant extracts. The wing somatic mutation and recombination test (SMART) using Drosophila melanogaster is a short term test suited for the detection of genotoxic activity of pure compounds or complex mixtures as well as for studies on antigenotoxicity. The SMART was used to evaluate the genotoxicity of EE obtained from the leaves or fruits of A. trinervis and EE from the leaves or stem of N. cissiflora as well as of g-lactones (isoobtusilactone) isolated from fruits of A. trinervis. The extracts and the g- lactone fraction showed no mutagenic effects on spontaneous DNA lesions. Due to these preliminary observed results, EE from the leaves of A. trinervis and EE from the leaves or stem of N. cissiflora were used in combination with the free radical generator doxorubicin (DXR) (used as chemotherapeutic agent) for antigenotoxic evaluation. All in all, when EE were combined with DXR, the results generally indicated a dose-related antigenotoxic (antimutagenic) effects, which depends on to different secondary metabolites found in each type of extract, which probably operate through different mechanisms of action.